Communication Evaluation: Case Study of Program Implementation Green Youth Movement (GYM) Ministry of Environment and Forestry - Sri Mulyani (CV. Publikasi Indonesia, 2025)
The research aims to evaluate the effectiveness of the Green Youth Movement (GYM) program in increasing Generation Z's participation in environmental issues. Although Generation Z shows a high awareness of environmental problems, their participation in conservation activities remains relatively low. The research methods used include Focus Group Discussions (FGD), interviews, and analysis of activity reports to gather qualitative information regarding the motivations, perceptions, and experiences of participants. The results indicate a gap between awareness and actual actions, as well as the importance of transparency and accountability in programs involving Generation Z. Additionally, the use of social media as a communication tool and information dissemination has proven effective in reaching a young audience. The recommendations produced include the need to create interactive platforms for Generation Z's involvement in program planning, as well as conducting regular evaluations and adaptations of communication strategies. This research is expected to make a significant contribution to the development of more inclusive and responsive environmental policies that align with the aspirations of Indonesia's youth.